Greening the fringes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The United Nations Environment Programme (UNEP) is spending US$ 50 million on a new phase of the Desert Margins Programme. The programme will marry indigenous knowledge with modern land management techniques to find new ways of protecting the...